Multi‐Component Reaction of 6‐Aminouracils, Aldehydes and Secondary Amines: Conversion of the Products into Pyrimido[4, 5‐d]pyrimidines through C‐H Amination/Cyclization. Issue 12 (25th March 2019) - Borpatra, Paran J.; Rastogi, Gaurav K.; Saikia, Ms. B‐S.; Deb, Mohit L.; Baruah, Pranjal K.
Abstract: Reaction of 6‐aminouracils with aldehydes and secondary amines catalyzed by acetic acid is reported here. This is in fact a domino aza‐Michael reaction. 6‐Aminouracil reacts first with aldehyde and then amine attacks the newly formed C=C bond, which is established from the mass spectral analysis of the reaction mixture. The products of the reaction are cyclized to pyrimido[4, 5‐ d ]‐pyrimidines via intramolecular α‐C−H functionalization of tertiary amine promoted by I2 ‐TBHP at room temperature in ethanol solvent. I2 (10 mol %) and TBHP (1.5 eq.) are used for the cyclization reactions. Based on few controlled experiments a tentative radical mechanism is proposed for the cyclization step. Abstract : We have developed multi‐component domino aza‐Michael reaction of 6‐aminouracils with aldehydes and secondary amines. These aza‐Michael products were further converted to pyrimido[4, 5‐ d ]pyrimidines using metal‐free intramolecular C−H functionalization. The reactions are performed at room temperature using ethanol as solvent.